Analisis Perilaku Harga Saham, Volume Perdagangan, dan Abnormal Return Sebelum dan Sesudah Ex-Dividend Date: Studi pada Emiten Bank Buku 4 Periode 2020-2024 - A'la Abid; Syti Sarah Maesaroh; Nugraha Adhi Pratama (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study investigates differences in stock prices, trading volume activity (TVA), and abnormal returns before and after the ex-dividend date among Bank BUKU 4 companies listed on the Indonesia Stock Exchange during 2020-2024. The research was motivated by inconsistent findings in previous studies regarding market reactions to ex-dividend events, particularly in the banking sector during the post-pandemic period. A quantitative approach with an event study method was employed using a 10-day event window, consisting of five trading days before and five trading days after the ex-dividend date. The sample included four major Indonesian banks, namely BBCA, BBRI, BBNI, and BMRI, selected through purposive sampling. Secondary data were obtained from the Indonesia Stock Exchange, KSEI, and Yahoo Finance. Data analysis was conducted using the Kolmogorov–Smirnov normality test, followed by the Wilcoxon Signed Rank Test and Paired Sample t-Test. The results indicate significant differences in stock prices and trading volume activity after the ex-dividend date, while abnormal returns do not show significant differences. These findings suggest that ex-dividend events influence market activity and investor trading behavior, although they do not generate excess returns in the observed banking sector.